101 leadership actions for effective presentations - Malone, Ollie (HRD Press, 2004)
Upgrade your leadership skills quickly and easily?and produce results in your organization with a lot less effort. Each book in this collection focuses on a specific area of leadership and managerial effectiveness and offers 101 actions you can accomplish today to improve your impact. The books are easy-to-read and written by experts with real-world experience. Packed with involving activities that encourage thought and action, the books offer techniques that have been tried and proven effective in Fortune 500 companies. Read each title from cover to cover or one action-at-a-time. Either way, you are sure to discover new and stimulating ways to unleash your best effort as a leader. Organize your presentation thoughts ... present your ideas with impact ... manage yourself and your audience. These 101 actions will help you overcome?presentation-dread.? Get ideas on how to make your main point compelling, practice with tape recorders and video recorders, use memory joggers, create slides, and more.